ANALISIS KEMAMPUAN SISWA DALAM MENYELESAIKAN SOAL UN FISIKA SMA PADA MATERI MEDAN MAGNET BERDASARKAN TAHAPAN POLYA - Esa Ria Permata Hati; Bambang Supriadi; Alex Harijanto (JURNAL PEMBELAJARAN FISIKA, 2018)
This research to describe the ability of students in solving National Examination Physics Senior High School problems on Magnetic Field based on Polya steps. The sample of this research using purposive sampling based on permission from school. Schools were use as research that were school A and B in Jember District by choosing one class XII to be the subject of research. The collected technique in this research used the test in the form of description, interview, and documentation. The percentage of students’s ability in solving the problem was known from the completion of the students in solving the problem on the problem solved sheet which has been based on Polya stage. The average percentage of students’s ability in solving the problem of National Examination Physics High School on Magnetic Field based on Polya stages in SMAN A, there were step of understanded the problem of 76.67%, the step of devised a plan of 22.93%, the step of carried out the plan of 53.73 %, and looked back step of 7.07%. While the average percentage of students's ability in solving the problem of National Examination Physics High School on Magnetic Field based on Polya stages in SMAN B, there were step understanded of the problem of 70.34%, the step of devised a plan of 32.00%, the step of carried out the plan of 84, 55%, and looked back step of 6.21%.Key word: Polya steps, National Examination problems, Magnetic Field, ability of students in solving problems